Pengaruh Gaya Kepemimpinan Transaksional, Transformasional, Kepuasan Kerja, dan Beban Kerja terhadap Kinerja serta Intensi Pindah Kerja Perawat di RSUD Sabang - Ariyani Ariyani; Sri Lestari Ramadhani Nasution; Ermi Girsang (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Nurse performance and turnover intention are critical issues in hospital human resource management, influenced by leadership style, job satisfaction, and workload. Objective: This study aimed to analyze the effects of transactional and transformational leadership styles, job satisfaction, and workload on nurse performance and turnover intention at Sabang Regional General Hospital (RSUD Kota Sabang). Methods: A quantitative analytic design with a cross-sectional approach was employed. The study population and sample comprised all staff nurses in the inpatient units of RSUD Kota Sabang using total sampling (n=120). Data were collected using standardized Likert scale questionnaires (1–5), adapted from the Multifactor Leadership Questionnaire (MLQ) by Bass & Avolio, the Job Descriptive Index (JDI), and a validated turnover intention instrument. Multiple linear regression analysis was performed following normality, linearity, and multicollinearity testing. Results: Simultaneously, all four independent variables significantly influenced nurse performance (Sig.=0.037; R²=3.8%) and turnover intention (Sig.=0.032; R²=2.8%). In partial analysis, transformational leadership demonstrated the strongest positive effect on performance (B=0.211; Sig.=0.002) and the strongest negative effect on turnover intention (B=-0.111; Sig.=0.030). Workload was the most dominant predictor of performance decline (B=-0.186; Sig.=0.035), while job satisfaction was the most significant predictor of nurse retention (B=-0.110; Sig.=0.014). Conclusion: Transformational leadership and workload management represent priority interventions for improving nurse performance and reducing turnover intention. The low R² values indicate the need for further research integrating organizational culture, remuneration systems, and individual factors into the explanatory model.